2019
DOI: 10.26554/sti.2019.4.1.1-4
|View full text |Cite
|
Sign up to set email alerts
|

Alpha Glukosidase Inhibitory Test and Total Phenolic Content of Ethanol Extract of Parkia Speciosa Plant

Abstract: Parkia speciosa (Fabaceae),  much grow in South Sumatera. The seed of P. speciosa used as traditional medicine for  diabetes mellitus therapy. Another parts of P speciosa is suspected to have the same chemical compounds and potency as the seed. Based on phytochemical screening of leaf and rind of P speciosa have secondary metabolites as flavonoid, phenolic and terpenoid.  This research aims to know effectiveness of alpha glucosidase inhibitory effect of ethanol extract of rind, leaf and  seed of  p. speciosa a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Six studies comprising three in vitro and three in vivo studies have demonstrated hypoglycemic activity of the plant, but no clinical study has been conducted. Most of the studies have studied the activity in the seeds and pods [ 120 , 156 , 157 , 158 ].…”
Section: Pharmacological Activities Of Parkia Smentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies comprising three in vitro and three in vivo studies have demonstrated hypoglycemic activity of the plant, but no clinical study has been conducted. Most of the studies have studied the activity in the seeds and pods [ 120 , 156 , 157 , 158 ].…”
Section: Pharmacological Activities Of Parkia Smentioning
confidence: 99%
“…The seeds also show inhibitory activity but at lower percentage (45.72%) [ 156 ]. In another study, the ethanol extract of the rind had the highest α-glucosidase inhibitory activity followed by the leaf and seed with IC 50 of 4596 ppm, 54,341 ppm, and 67,425 ppm, respectively as compared with acarbose having 162,508 ppm [ 158 ].…”
Section: Pharmacological Activities Of Parkia Smentioning
confidence: 99%
“…One kg of dry Benalu leaf powder was extracted by maceration method using 3 L of 70% ethanol three times. After filtering, the total filtrate was evaporated with a rotavapor (Yamato® RE301) to obtain an ethanol extract of Benalu leaves (EDP) (Fitrya et al, 2019) .…”
Section: Extract Preparationmentioning
confidence: 99%
“…Traditionally, these plant seeds have been used by locals to treat various diseases and symptoms like diabetes, kidney disorder, headache, hypertension, skin problems, and diarrhea [ 6 , 7 , 8 ]. Scientifically, P. speciosa has been reported to possess hypoglycemic [ 9 , 10 , 11 ], antioxidant [ 8 , 12 , 13 , 14 , 15 ], anti-inflammatory [ 16 , 17 ], and antihypertensive [ 18 , 19 ] properties. The polyphenols found in this plant include gallic acid, ellagic acid, catechin, quercetin, vanillic acid, and epicatechin [ 19 ].…”
Section: Introductionmentioning
confidence: 99%